Structural characterisation and photophysical properties of lanthanoid complexes of a tetra-amide functionalised calix[4]arene - Driscoll, C.; Skelton, B.; Massi, Massimiliano; Ogden, Mark (Taylor and Francis Ltd, 2016)
Lanthanoid complexes of a tetra-amide substituted calix[4]arene in the cone conformation are characterised by single crystal X-ray structure determination. The structural analysis shows that the metal ions are coordinated to the calixarene through the eight O donor atoms, along with one aqua ligand which is located within the cavity of the calixarene. The calixarene ligand was covalently incorporated into a polymethylmethacrylate monolith through p-allyl functional groups, followed by loading with a range of lanthanoid cations giving rise to light-emitting materials. The emission from the hydrid materials was found to be comparable to the solution phase emission.